The White Presence on the Black Campus Some Questions and Answers - Brown, Charles I.; National Association for Equal Opportunity in Higher Education, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
Findings regarding white students, faculty, and administrators on the black college campus are reviewed. Studies indicate that the typical white student at a traditionally black campus in the South is a native of the Southern region, 27-30 years old, and likely to be married. The student has both pleasant and unpleasant experiences related to problems of adjustment and acceptance, and usually has not sought special help. White students often attend the black college primarily to get an education and not to participate in social or extracurricular activities. The most comprehensive profile of the white faculty on the black campus has been drawn by Paul Decker (1955), who investigated 20 colleges in 10 states. Principal findings include the following: 40 percent had no particular reason for working in a black college; 20 percent were working because of an interest in race relations; teachers did not think of their students in terms of race any more than do other teachers; relationships with students were close and rewarding; 95 percent of the white teachers claimed good rapport with their black colleagues; and 64 percent lived in a black community. Findings of a survey of white administrators at several public and private historically black institutions included the following: 53 percent of the administrators stated that their institution actively recruited white students; white students' chief adjustment problem after enrollment was their reluctance to express opinions freely in front of black classmates and black professors; and 59 percent of the administrators felt their campuses did not need a special orientation program solely for white students. (SW)
ERIC Note: This paper was identified by a joint project of the Institute on Desegregation at North Carolina Central University and the ERIC Clearinghouse on Higher Education at The George Washington University. The paper was also presented at the Annual Meeting of the National Association for Equal Opportunity in Higher Education (3rd, Washington, DC, April 29, 1978).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Administrators; Black Colleges; Black Students; Black Teachers; College Desegregation; College Environment; College Faculty; College Students; Higher Education; Racial Relations; Student Attitudes; Student College Relationship; Student Educational Objectives; Student Teacher Relationship; Teacher Attitudes; Whites; Information Analyses; Speeches/Meeting Papers